Effect of Service Quality, Product Quality and Brand Image on Purchase Decisions in Pt. POS Indonesia 61100 Gresik - Ilham Amani Nurfi; Moh Agung Surianto (Universitas Muhammadiyah Gresik, 2021)
The background of this study is that many students have not met the Standards ofGrades. Then the purpose of this study was to determine the effect of parents' attention,learning motivation and discipline on student achievement in SMAN 3 Lamongan. The sampleusing proportionate stratified random sampling method is a sampling technique that is carriedout if the traits or elements in the population are not homogeneous and stratified less ordisproportionately while measuring data using the Likert scale. Technical analysis uses theinstrument test (validity test and reliability test) to test the quality and consistency of themeasuring instrument, the model test / classical assumption test (normality test,multicollinearity test and heterokedasticity test). The results of the study stated that ParentalAttention, Learning Motivation and Discipline had a positive and significant effect on StudentAchievement in SMAN 3 Lamngan Students.